Reinforcing supramolecular hyaluronan hydrogels via kinetically interlocking multiple-units strategy. (15th June 2023) - Chen, Ruofan; Li, Yujie; Jin, Yu; Sun, Yawei; Zhao, Zhiyong; Xu, Yun; Xu, Jiang-Fei; Dong, Yuanchen; Liu, Dongsheng
Abstract: Supramolecular hydrogels exhibit promising potential in biological and clinical fields due to their special dynamic properties. However, most existing supramolecular hydrogels suffer from poor mechanical strength, which severely limits their applications. Here in this study, the Kinetically Interlocking Multiple-Units (KIMU) strategy was applied to the hyaluronan networks by introducing different supramolecular interaction motifs in an organized and alternative manner. Our strategy successfully elevated the energy barrier of crosslinker dissociation to 103.0 kJ mol -1 and increased the storage modulus of hydrogels by 78 % with the intrinsic dynamic properties preserved. It can be expected that this method would bring a convenient and effective route to fabricate novel supramolecular materials with excellent mechanical properties. Graphical abstract: Unlabelled Image